C-kit expression in human osteosarcoma and in vitro assays - Miiji, Luciana Nakao Odashiro [UNIFESP] (2011)
Biologic agents targeting oncogenes have encourage researchs trying to correlate the role of tyrosine kinase in the pathogenesis of tumours. Osteosarcoma is a high grade aggressive neoplasm with poor survival. Our aim was to investigate c-kit immunoexpression, its prognostic relevance for patients with osteosarcoma, and the effect of imatinib mesylate (STI571) on proliferation and invasion of the human osteosarcoma cell line. A retrospective immunohistochemical study was performed on archival formalin-fixed paraffin-embedded specimens from 52 patients with high-grade primary osteosarcoma of extremities treated at the Pediatric Oncology Institute (IOP, GRAAC) and archived in the Department of Pathology, Federal University of Sao Paulo. Only pre-chemotherapy specimens were analyzed. Strongly stained cytoplasm and membrane cells were taken as positive. Human osteosarcoma cells from line MG-63 were incubated and the inhibitory effect of imatinib mesylate (STI571) on cell proliferation and invasion was studied. In 24 cases (46.15%), c-kit was expressed by the cells and c-kit-positive tumors exhibited lower necrosis post-chemotherapy. No correlation was found between c-kit expression and overall and disease-free survival. Imatinib mesylate decreased the rates of cell growth of osteosarcoma cells in low doses and invasion in high doses C-kit-positive tumors had worse response to chemotherapy and imatinib mesylate can play a role in blocking or decreasing the rate of growth of osteosarcoma cells, but not the invasive capacity of these neoplastic cells. These data suggested that imatinib mesylate could be a therapeutic target of strategies against osteosarcoma tumors. Further studies are necessary to confirm this indication.